A Proposal for the Implementation of an English for Specific Purposes Specialization in a Master's Degree Program in Second Languages and Cultures with Emphasis in English as a Foreign Language - Saborío Pérez, Ileana (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2009)
.